2013
DOI: 10.1590/1516-4446-2012-0907
|View full text |Cite
|
Sign up to set email alerts
|

Outcome predictors of smoking cessation treatment provided by an addiction care unit between 2007 and 2010

Abstract: Objective: To analyze the predictors of smoking cessation treatment outcomes in a sample with a high rate of medical and psychiatric disorders and addictions. Methods: Analysis of predictors of success of a 6-week treatment provided by an addiction care unit (CAPS-AD) to 367 smokers in Brazil from 2007 to 2010. Forty variables were collected at baseline. Success was defined as abstinence from smoking for a period of at least 14 consecutive days, including the last day of treatment. Twenty variables were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
0
18
0
2
Order By: Relevance
“…Secondly, although several researches [2123] recommended the expired CO-verified 24-hour point abstinence rate as primary outcome measure to ensure the objectivity and correctness, we noted that failed subjects could be considered as successful by CO-verified 24-hour point abstinence rate if they kept nonsmoking status within 24 hours before evaluation and smoked before and after that, which overrated the curative effects of acupuncture. In this study, self-reported 7-day point abstinence rate combined with verification of expired CO could reflect the effects of acupuncture more correctly.…”
Section: Discussionmentioning
confidence: 88%
“…Secondly, although several researches [2123] recommended the expired CO-verified 24-hour point abstinence rate as primary outcome measure to ensure the objectivity and correctness, we noted that failed subjects could be considered as successful by CO-verified 24-hour point abstinence rate if they kept nonsmoking status within 24 hours before evaluation and smoked before and after that, which overrated the curative effects of acupuncture. In this study, self-reported 7-day point abstinence rate combined with verification of expired CO could reflect the effects of acupuncture more correctly.…”
Section: Discussionmentioning
confidence: 88%
“…Although the death rate estimated by cocaine is lower than death rates from other drugs (Warner et al, 2011), and was in decline in the last decade (Centers for Disease Control and Prevention, 2011), it is likely that there was no death in the analysed sample. The naturalistic nature of the study is a limitation, but also a strength, of the study since this allows an analysis of data from the real world, which is needed for the progress of translational science (Michelson et al, 2013), especially in public mental health (Castaldelli-Maia et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…This law determines the spread of Centros de Atenção Psicossocial (CAPS; in english: psychosocial support centers) as the main point of this new mental health-care system and care delivery. These care outpatient units were designed to promote comprehensive care for people with severe mental disorders, including alcohol and drug addiction (Castaldelli-Maia et al, 2013). They are expected to enable patients to access their civil rights, education, employment and education in order to live in society.…”
Section: The Impact Of Basaglia On Brazilian Psychiatrymentioning
confidence: 99%